DENTAL FLUOROSIS AND THE PREVALENCE OF DENTAL CARIES IN CHILDREN AGE ON 6-16 - A/P Sivakumar, Nathasha; Jaganathan, Nithya; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Fluoride is a double-edged sword. The fluoride produces a dose-dependent effect on the teeth. However, this is not confined to increased caries resistance. Fluoride causes various disorders, together called fluorosis, if accumulated above certain levels in the body. The aim of the study is to assess the dental caries and dental fluorosis prevalence among 6 to 15-year-old schoolchildren. 50 schoolchildren in the age group of 6-16 years were selected for the study and were divided into six age groups. The children were assessed for dental fluorosis according to Dean’s criteria Index of Fluorosis and dental caries according to WHO basic survey guidelines. The overall health status of the child was assessed by the DMFT index. The results of the present study revealed that the prevalence of grade 2 fluorosis was the highest and grade 5 fluorosis was the lowest in all the age groups. The number of children was highest in the age group between 15-16 years, followed by the age group between 6 and 7 years. The overall DMFT increased as the age of the children increased in the different age groups. The DMFT increased as the severity of fluorosis increased up to grade 2 and then decreased from grade 3 to grade 5. In conclusion, my findings showed that the risk of dental fluorosis was significantly higher in the areas showing more fluoride content in drinking water and to a lesser degree of dental caries in the same area. There was also an increased problem of dental fluorosis with the passage of time. It is recommended to reduce the fluoride content of drinking water in the high fluoride area by making either alternative sources available or providing water with reduced fluoride content.